PENGARUH TEKNIK BACK MASSAGE (MASASE PUNGGUNG) TERHADAP PENURUNAN INTENSITAS NYERI PADA PASIEN POST OPERASI APPENDIKSITIS DI RSU ROYAL PRIMA MEDAN 2018 - Nababan, Tiarnida; Kaban, Karmila (Jurnal Keperawatan Priority, 2019)
Pain is an unpleasant sensory and emotional experience due to actual and potential tissue damage. One of the non-pharmacological therapies to deal with pain is the back massage technique. The technique can reduce the intensity of pain in postoperative appendicitis patients so that the therapy can provide comfort for the patient. This study aims to explore the effect of back massage technique on reducing pain intensity in patients with postoperative appendicitis. This type of research is pre-experimental using a one-group pre-post design test. The research population included 13 patients postoperative appendicitis at Royal Prima Hospital Medan in 2018. The research samples were drawn by using the Accidental Sampling technique. The research was conducted on March 2018 at Royal Prima hospital Medan. The research data were analyzed using Wilcoxon Test with a significant value of α = 0.05. The patient experienced pain before back massage was provided and after the administration of back massage technique, patient experiencing mild pain was 60% and 40% experienced moderate pain. The results of bivariate analysis showed that p-value = 0.034. This showed that there was a difference between the intensity of pain before and after the back massage technique was performed in patients with postoperative appendicitis. From the results of the above research, it is suggested that the implementation of back massage techniques has an effect on the decrease in pain intensity in patients with postoperative appendicitis. This back massage technique can be applied at hospitals as a measure of pain management which is an independent action of the nurse to handle the patient's pain.